Prevalence and factors associated with smoking among adolescents, - Marilyn Urrutia-Pereira; Vinicius J. Oliano; Carolina S. Aranda; Javier Mallol; Dirceu Solé
Abstract Objective: Despite anti-smoking prevention programs, many adolescents start smoking at school age. The main objectives of this study were to determine the prevalence and risk factors associated with smoking in adolescents living in Uruguaiana, RS, Brazil. Methods: A prospective study was conducted in adolescents (12-19 years), enrolled in municipal schools, who answered a self-administered questionnaire on smoking. Results: 798 adolescents were enrolled in the study, with equal distribution between genders. The tobacco experimentation frequency (ever tried a cigarette, even one or two puffs) was 29.3%; 14.5% started smoking before 12 years of age and 13.0% reported smoking at least one cigarette/day last month. Having a smoking friend (OR: 5.67, 95% CI: 2.06-7.09), having cigarettes offered by friends (OR: 4.21, 95% CI: 2.46-5.76) and having easy access to cigarettes (OR: 3.82, 95% CI: 1.22-5.41) was identified as factors associated with smoking. Having parental guidance on smoking (OR: 0.67, 95% CI: 0.45-0.77), having no contact with cigarettes at home in the last week (OR: 0.51, 95% CI: 0.11-0.79) and knowing about the dangers of electronic cigarettes (OR: 0.88, 95% CI: 0.21-0.92) were identified as protection factors. Conclusion: The prevalence of smoking among adolescents in Uruguaiana is high. The implementation of measures to reduce/stop tobacco use and its new forms of consumption, such as electronic cigarettes and hookah, are urgent and imperative in schools.